Peningkatan Pendapatan Petani Tembakau melalui Penerapan Teknologi Mesin Perajang Daun Tembakau di Kecamatan Purbolinggo Kabupaten Lampung Timur - Yuliawan, Dedy; Warji, Warji; Wanniatie, Veronica (Jurnal PKM Manajemen Bisnis, 2025)
Tobacco is one of the agricultural products that serves as a main commodity for farmers in Purbolinggo District, East Lampung Regency. East Lampung Regency is the largest tobacco-producing area in Lampung Province. This Community Service activity aims to provide training on tobacco cutting machine technology, tobacco marketing, and to disseminate information by introducing tobacco cutting machine technology. This service is beneficial for tobacco farmers as it reduces the time required for cutting tobacco, which positively impacts the quantity of cigarette production and increases farmers' income. The results of the community service conducted by the University of Lampung team in Taman Cari Village, Purbolinggo District, East Lampung Regency provide significant benefits for tobacco farmers in processing tobacco leaves into ready-to-roll tobacco (TSG).